ANALYSIS OF THE EFFECT OF KOHESIVITAS GROUPS AND EFFECTIVENESS OF TEACHER WORK PRODUCTIVITY - Juliana Hakim; Matin Matin; Supadi Supadi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The objective of the research is to obtain information about the influence of group cohesiveness and team effectiveness on teachers' productivity of state primary school at Cipondoh districts in Tangerang City. The research was conducted to all of state primary school teachers at Cipondoh districts in Tangerang City by using a survey method with path analysis applied in testing hypothesis. The number 98 teachers as sample was selected by using Slovin formula. The result of the study reveals that: (1) there is direct effect of group cohesiveness on teachers' productivity. (2) there is direct effect of team effectiveness on teachers' productivity. (3) there is direct effect of group cohesiveness on team effectiveness. Therefore to enhance teachers' productivity can be carried out by group cohesiveness and team effectiveness. Keywords: Group cohesiveness, team effectiveness, and teachers' productivity